LEBANESE IN THE GULF STATES - Farhat, Tamara (2022)
Lebanese migration to the Gulf states is a phenomenon that passed throughout different waves starting from the era of the late years of the Ottoman Empire till the present day. It has been impacted by many socio-political factors. This thesis aims to gain a better understanding of the Lebanese diaspora identity in these states where social integration mechanisms are constantly obstructed. To achieve this objective, an extensive literature review is conducted on waves of Lebanese migration to the Gulf, the integration of the Lebanese migrants in these states or lack thereof, and their social identity and sense of belonging. In this context, the thesis draws on existing literature that discusses integration policies followed by the Gulf states. It also discusses the bilateral relationship between Lebanon and Gulf Cooperation Council (GCC) countries, and the Lebanese migration outflows to the Gulf that persisted despite the diplomatic crisis between the two countries. Based on the conducted research targeting the Lebanese diaspora living in the United Arab Emirates (UAE) as a case study, it was found that the identity of Lebanese migrants and their sense of belonging are obstructed by social traditions as well as policies and regulations of the GCC countries. This thesis concludes by explaining the actual reality of the Lebanese migrant’s identity living in the Gulf and concluding that it as an identity dwelling in liminality.